Corals Habitat Formers in the Anthropocene - Chimienti, Giovanni (IntechOpen, 2023)
Corals have thrived on the bottom of the ocean for millions of years. These fascinating animals are currently forced to cope with the rapid changes caused by humans to avoid extinction. How are corals changing their way of processing energy from different sources? What do we know about the corals living in the unseen depths of certain seamounts? What is the impact of oil spills and what can we do? How are coral reefs all over the world to be restored? What is the socioeconomic importance of these habitats, and what do we gain or lose with their survival or their demise? By involving scientists and conservationists from different areas of the world, this book answers these and other questions about corals, the habitat they form, and the influence that we have on them.